절임 배추와 양념소가 김치 발효에 미치는 영향 - 윤자영(Ja-Young Yun); 정지강(Ji-Kang Jeong); 문숙희(Suk-Hee Moon); 박건영(Kun-Young Park) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2014)
This study investigated and compared the fermentation characteristics of intact kimchi and brined baechu cabbage and seasoning fermented separately. Fermentation characteristics of kimchi, brined baechu cabbage and seasoning, such as pH, acidity, microbial counts, and springiness were measured during the fermentation period (4 weeks at $4^{°}C$). Changes in pH, acidity, and microbial counts of the seasoning fermented separately were slower than those of brined baechu cabbage and kimchi itself. The fermentation characteristics of brined baechu cabbage were very similar to those of kimchi during the fermentation period. Additionally, we manufactured and fermented kimchi, after which baechu cabbage and seasoning were separated shortly before the measurements. Baechu cabbage and seasoning separated instantly from kimchi showed similar fermentation characteristics to their separately fermented counterparts. Changes in springiness of kimchi itself and brined baechu cabbage fermented separately were similar during the fermentation period. These results indicate that kimchi fermentation is affected by brined baechu cabbage more than seasoning. 김치를 절임 배추와 양념소로 각각 분리하여 발효하였을 때와 포기김치의 형태로 함께 발효하였을 때 그 품질특성이 어떻게 변화하는지를 $4^{°}C$에서 4주간 발효하면서 관찰하였다. 절임 배추, 양념소와 포기김치의 이화학적 특성으로는 pH, 산도, 총균 및 유산균의 수, 배추 조직의 탄력성 평가를 실시하였다. $4^{°}C$에서 4주간 저장한 양념소는 pH, 산도의 변화와 미생물수의 변화로 미루어 볼 때 절임 배추나 포기김치보다 발효가 더디게 진행되는 것을 알 수 있었다. $4^{°}C$에서 4주간 분리하여 저장한 절임 배추의 경우는 양념소에 비해 빠르게 발효가 진행되는 것을 알 수 있었으며 이것은 포기김치의 발효 양상과 거의 비슷한 경향을 보였다. 이로써 김치의 발효는 양념소에 의한 것보다는 배추에서 유래되는 영향이 더 큰 것으로 생각된다. 또한 포기김치의 형태로 저장한 이후 실험 직전에 절임 배추와 양념소를 따로 분리하여 그 발효 양상을 관찰하였다. 포기김치로부터 분리해낸 절임 배추와 양념소의 pH, 산도, 미생물수는 4주간 따로 저장한 절임 배추, 양념소와 비슷한 경향을 나타내어 따로 혹은 함께 발효를 진행하여도 그 발효 양상이 비슷함을 알 수 있었다. 또한 김치와 절임 배추 조직의 탄력성을 측정한 결과 4주간의 발효기간 동안 유의적인 차이를 보이지 않는 것으로 나타났다. 이를 바탕으로 김치의 발효는 양념소보다는 절임 배추에 의해 보다 큰 영향을 받는 것으로 생각된다.